RINONEUMONITIS EQUINA EN CABALLOS DEL VALLE DE LIMA - Ríos S., Paolo (2002)
The objective of this study was to determine the prevalence of the equine herpes virus type 1 (EHV-1 ), the causa ti ve agent of equine rhinopneumonitis, in mature healthy horses of various breeds reared in Lima valley, Peru. For this purpose serum samples (n = 448) were collected during October 2000 till March 2001 for detecting neutralizing antibodies against EHV-1 by virus neutralisation test. The prevalence ofEHV-1 was 44.2 ± 4.6%. The highest prevalence was detected in Standardbred (52.6%) followed by Thoroughbred (47.1 %) and Peruvian horses de Paso (34.8% ). Antibody titres against EHV-1 ranged between 2 to> 256. There was no statistical association between the presence of antibodies against EHV-1, sex, activity and location of the horses. This results indicate that the EHV-1 has wide distribution in horses reared in the Lima valley, Perú.